"Bringing the State Back In": Explaining Women's Economic Empowerment in an Era of Globalization. (November 2018) - Wang, Zhiyuan
The extant literature views the decision to protect women's economic rights as made by firms and neglects the role of the state. This study argues that states are pressured to improve the protection of these rights by enacting gender parity–promoting policies in response to similar policy choices by their economic competitors, resulting in a specific type of policy interdependence—the upward policy convergence. Additionally, this convergence should be stronger in laws than in practices because some states continue to benefit from women-suppressing policies, and because improving laws is less costly than improving policy implementation. Using newly coded global data from 1999 to 2009 on women's economic rights that distinguish between laws and practices, spatial econometrical analyses support these conjectures. Essentially, this study shows that the race to the bottom is not the sole consequence of globalization, a climb to the top is possible as well when we look closer and more carefully. In other words, trade and capital dependence can generate positive policy gains too.